Integrasi Prinsip Syariah pada Manajemen Kinerja Proyek CSR: Studi Kasus Sektor Pertambangan Indonesia - Aulia Dewi, Nurul; Majid, Shabri Abd; Sugianto, Sugianto (Forum Kerjasama Pendidikan Tinggi, 2025)
The mining industry in Indonesia plays a vital role in national economic development, yet it poses serious social and environmental challenges. Corporate Social Responsibility (CSR) practices have emerged as a strategic solution to bridge the interests of corporations and affected communities. This article aims to analyze how Sharia principles can be systematically integrated into the performance management of CSR projects within the mining sector. Through a qualitative, literature-based approach, this study finds that Sharia values such as amanah (trustworthiness), adl (justice), and ta'awun (cooperation), along with the maqasid al-shari'ah framework, serve as an essential foundation. Furthermore, evaluation models like the Sharia Triple Bottom Line and ESG-Sharia have been shown to broaden the scope of CSR performance to include a spiritual dimension. Supporting factors for its implementation include Islamic leadership and the encouragement of ethical investors, while key barriers are low Sharia literacy and the conflict between profit-orientation and ethical values. This study recommends the establishment of a national standard for Islamic CSR and the strengthening of practitioner capacity to achieve a more transformative, just, and sustainable CSR approach.